KENDALA-KENDALA PENGAJARAN BAHASA INDONESIA DI KOREA SELATAN - Ronidin Ronidin (JURNAL ARBITRER, 2015)
This article aims to describe the constraints of teaching Indonesian in South Korea in a qualitative and descriptive manner. They include the learning process in terms of linguistic and non-linguistic aspects. The data obtained through observation and written materials throughout the process of teaching in the Department of Interpretation and Translation of Malay-Indonesian, Hankuk University of Foreign Studies, Yongin, Korea and Indonesian Language Course for Regional Expert of Samsung at the same campus. The analysis results suggest that non-linguistic constraints consist of issues of cultural differences between Indonesia and Korea, strong influence of the environment that cause interference, and the negative impact of the use of the internet, especially when learners use google translation. Meanwhile, linguistic constraints include some aspects of language in the form of linguistic deviation such as language error. Frequent errors in the teaching process encompass error word choice, error sentence composition, error of affixes, and the error use of preposition.